ON NECESSARY AND SUFFICIENT CONDITIONS FOR DUALS OF WAVELET FRAMES - 张泽银 王建忠 (Acta mathematica scientia, 1995)
This paper is concerned with the characterization of the duals of wavelet frames of L2(R). The sufficient and necessary conditions for them are obtained.